The politicization of the Arctic in the beginning of the 21st century : how do the Arctic Ocean states legitimate their new role in the Arctic of melting ice and new opportunities? - Dahl, Justiina (fi=Lapin yliopisto|en=University of Lapland|, 2010)
The aim of research in this study is to explain why the Arctic region is in the beginning of the 21st century under politicization, and how the five Arctic Ocean states participate in it by actively legitimating their new leading role in the governance of the Arctic of melting ice and new opportunities. The previous politicization that the region underwent after the Cold War and the changed geopolitical framework for the new one are first written open in order to set the scene for analysis, which is done according to relational constructivist analysis. The historical account of the previous politicization of the region legitimates the claim of a new one and connects the study to other research done of the Arctic. It also helps to deepen the analysis from being mere explanation of activities in the Arctic into offering a more comprehensive understanding of the politicization processes taking place in the region. The theoretical framework of the study constructs of traditional and critical geopolitics and theories of governmentality. It also connects to the constructivist ontology of the study and to theories of legitimacy, which are used as an aid in the research methodology. The main body of work consists of the identification of legitimation discourses that the five littoral Arctic states use when participating in the construction and validation of their new role and identity in the Arctic at a moment of disrupting continuity that the region is undergoing. These discourses are in the analysis mapped out according to their content into story-lines, generative sorts of narratives that allow the actors to draw upon various discoursive categories to give meaning to phenomena. With the help of these story-lines “a rhetorical topography” of the Arctic constructed by the states in their policies is then created. The research material from which the discourses are mapped out into story-lines consists of the Arctic policies of the five Arctic Ocean states published in years 2008 and 2009. As the choice of research ...